Antibiotic resistance of vibrio parahaemolyticus isolated from cockles and shrimp sea food marketed in Selangor, Malaysia - Al-Othrubi, Saleh Mutahar Yahya; Cheah, Yoke Kqueen; Mirhosseini, Hamed; Abdulhadi, Yousr; Radu, Son (Omics Publishing Group, 2014)
Introduction: The main aim of this study is to determine the antibiotic profile of V. parahaemolyticus gastroenteritis associated with the consumption of contaminated shrimp and cockles marketed in Selangor Malaysia. V. parahaemolyticus is the leading cause of seafood-associated gastroenteritis in Asian Countries typically is associated with the consumption of raw shellfish and oysters specially shrimp and cockles. Rapid, sensitive and specific detection methods are needed to control V. parahaemolyticus infections. We describe a recognized the pathogenic V. parahaemolyticus in shrimp and cockles that will be the risk of gastroenteritis associated with the consumption of seafood marketed in Malaysia. Methods: This study was carried out between July 2011 and August 2013 at the Center of Excellence for Food Safety Research, Faculty of Food Science and Technology, Faculty of Medicine and Health Sciences, Department of Biomedical Sciences, and Faculty of Biotechnology, Dep. of Cell and Molecular Biology, University Putra Malaysia and other centers as collaboration. The seafood samples were collected from different markets and more than 400 samples from shrimp and cockles were investigated for detection and isolation of V. parahaemolyticus. CHROMagar Vibrio and TCBS agar media were used for fast detection and isolation of V. parahaemolyticus isolates. PCR based methods targeted to toxR regulatory gene, tlh the species and family gene, tdh and trh the virulence genes were extensively used. The antibiotic susceptibility testing of 65 V. parahaemolyticus isolates recovered from retail shrimp and cockles seafood were determined with four types of E-test antibiotic strips. Results: All the 65 isolates were positive to toxR and tlh genes. Out of 65 isolates, only eight isolates (12.31%) were positive for tdh virulence gene isolated form cockles and shrimp (3 isolates from shrimp and 5 isolates from cockles), whereas twenty six (40%) isolates were positive for trh virulence gene isolated from shrimp and cockles (9 from shrimp and 17 from cockles). This result indicates high occurrence of tdh+ and trh+ isolates in shrimp and cockles marketed in Malaysia. None of the isolates tested possess both virulence genes. For the antibiotic E-test susceptibility test, overall, V. parahaemolyticus is remained susceptible to tetracycline (97%). A slight increase in the susceptibility of tetracycline is observed from 2011 to 2013. While reduced susceptibility was detected only in V. parahaemolyticus for ampicillin. The mean of MIC of the isolates toward ampicillin is increased from 64 μg/ml in 2011 to 128 μg/ml in year 2013. The current study demonstrates a high risk of pathogenic V. parahaemolyticus in the shrimp and cockles marketed in Selangor Malaysia. Conclusions: The potential risk of V. parahaemolyticus infection due to the consumption of contaminated seafood in Malaysia should not be neglected. The increased resistance of ampicilin from our studies in Malaysia since 2004 to 2013 could be in indication of antibiotic abuse in clinical and agricultural used of ampicilin in Malaysia.